La Revista de la Escuela Superior de Guerra "Tte Grl Luis María Campos" ; no. 598/2018 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (2018)
Ejemplar completo: Revista de la ESG. Año 95, no. 598 (ene-abr 2018). 78 p.